Rumen Microbiome and Metabolome of Tibetan Sheep (Ovis aries) Reflect Animal Age and Nutritional Requirement - Li, Huan; Yu, Qiaoling; Li, Tongtong; Shao, Liye; Su, Ming; Zhou, Huakun; Qu, Jiapeng (Frontiers in Veterinary Science, 2020)
The rumen microbiota plays an important role in animal functional attributes. These microbes are indispensable for the normal physiological development of the rumen, and may also convert the plant polysaccharides from grass into available milk and meat, making it highly valuable to humans. Exploring the microbial composition and metabolites of rumen across developmental stages is important for understanding ruminant nutrition and metabolism. However, relatively few reports have investigated the microbiome and metabolites across developmental stages in ruminants. Using 16S rRNA gene sequnecing, metabolomics and high-performance liquid chromatography techniques, we compared the rumen microbiota, metabolites and short chain fatty acids (SCFAs) between lambs and sub-adult Tibetan sheep (Ovis aries) from Qinghai-Tibetan Plateau. Bacteroidetes and Spirochaetae were enriched in sub-adult sheep, while Firmicutes and Tenericutes were more abundant in young individuals. The sub-adult individuals had higher alpha diversity values than those in young sheep. Metabolomics analysis showed that the content of essential amino acids and related gene functional pathways in rumen were different between the lambs and sub-adult population. L-Leucine that participates in valine, leucine and isoleucine biosynthesis was more abundant in the lambs, while phenylethylamine that takes part in phenylalanine metabolism was more enriched in the sub-adults. Both rumen microbial community structures and metabolite profiles were impacted by age, but rumen SCFA concentration was relatively stable between different age stages. Some specific microbes (e.g., Clostridium and Ruminococcaceae) were positively associated with L-Leucine but negatively correlated with phenylethylamine, implying that rumen microbes may play different roles for metabolite production at different ages. Mantel test analysis showed that rumen microbiota was significantly correlated with metabolomics and SCFA profiles.Our results indicates the close relationship between microbial composition and metabolites, and also reveal different nutritional requirement for different ages in ruminants, thus having important significance for regulating animal nutrition and metabolism by microbiome intervention.